# Week 4 Composition Function Presentation

Content type
User Generated
Subject
Mathematics
Type
Presentation
Rating
Showing Page:
1/22

Showing Page:
2/22

Showing Page:
3/22

End of Preview - Want to read all 22 pages?
Access Now
Unformatted Attachment Preview
Week 4 3.4 and 3.7 3.4 HW 1, 11, 21, 31, 41, 51, 61, 71, 81, 91, 93, 97 For two functions f(x) and g(x) with real number outputs, the following equations are true: ( f + g ) (x) = f(x) + g(x) ( f - g ) (x) = f(x) - g(x) ( fg ) (x) = f(x) g(x) ( f / g ) (x) = f(x) / g(x), where g(x) does not equal 0 Example 1… Find and simplify the functions (g-f)(x) and (g/f)(x), given f(x) = x - 1 and g(x) = x2 - 1. Are they the same function? (g - f)(x) = g(x) - f(x) = x2 - 1 - ( x - 1) = x2 - 1 - x + 1 = x2 - x = x ( x - 1) (g/f)(x) = g(x) / f(x) = ( x2 - 1 ) / ( x - 1 ) = ( (x-1)(x+1) ) / ( x - 1 ) = x + 1 No, these are not the same function Composition Function Combining functions so that the output of one function becomes the input of another function; binary operation that combines the functions (f∘g)(x)=f(g(x)) This can be read at “ f of g of x “ Always solve the inside function first and then input the output of that function into the outside function NOTE: f(g(x)) is almost never equal to g(f(x)) Example 2 Using the functions provided, find f ( g(x) ) and g ( f(x) ). Determine whether the composition function is commutative (def. The same or equal) f(x) = 2x + 1 g(x) = 3 - x f(g(x)) = 2(g(x) + 1 = 2 ( 3 - x ) + 1 = 6 - 2x + 1 = 7 - 2x g(f(x)) = 3 - (f(x) = 3 - ( 2x + 1 ) = 3 - 2x - 1 = 2 - 2x These equations are not equal and therefore are not commutative Example 4 Suppose f(x) gives miles that can be driven in x hours and g(y) gives the gallons of gas u ...
Purchase document to see full attachment
User generated content is uploaded by users for the purposes of learning and should be used following Studypool's honor code & terms of service.

### Review

Anonymous
Just what I needed…Fantastic!

Studypool
4.7
Indeed
4.5
Sitejabber
4.4